PERAN TOKOH MASYARAKAT DALAM MENGATASI PRAKTIK MAGI HITAM DI SIMEULUE - Husna Amin (Prodi Studi Agama-Agama, 2021)
Black Magi is a practice that uses supernatural powers for nefarious purposes. The practice of Black Magi is usually directed at others for various reasons, such as feelings of revenge, hate or for failing to have a girl, or simply testing the power of Black Magi science that a person who practices it has. The practice of Black Magi is usually intended to harm others, both physically and mentally. If a person is exposed to Black Magi, it can suddenly go crazy, the stomach enlarges, even until the body blisters, until it emits a foul smell and blood. The disease if it has been hit is difficult to cure. Diseases that are unpretentiously created by using the devil as a source of strength, it is very difficult to cure, so many are sick to chronic, even to death. The phenomenon of Black Magi practice is still found in Central Simeulue Subdistrict, Simeulue Regency, especially in Luan Sorip, Lauke, and Situfa Jaya Villages. the author is interested in further reviewing this. The study tries to explore how public figures view the practice of Black Magi and what efforts have been made to address it. This study is the result of field research using phenomenological approach. The data was obtained by direct observation and in-depth interviews with several community leaders, especially the victims' families. The results of this study are expected to find solutive alternatives that can be offered to the public, so that the Black Magi can at least be bridged, if it can not be eliminated.